An Electrochemical Study of the Corrosion Behaviour of T91 Steel in Molten Nitrates - D. Lopez-Dominguez; N. B. Gomez-Guzman; J. Porcayo-Calderón; R. Lopez-Sesenes; A. K. Larios-Galvez; E. Sarmiento-Bustos; E. Rodriguez-Clemente; J. G. Gonzalez-Rodriguez (Metals, 2023)
A study of the corrosion behaviour of T91 steel in molten 60 wt% NaNO3-40%KNO3 has been carried out at 300, 400 and 500 °C during 1000 h. Employed techniques included potentiodynamic polarization tests, linear polarization resistance (LPR) and electrochemical impedance spectroscopy (EIS) measurements. Experiments were complemented by detailed scanning electronic measurements and X-ray diffraction studies. Polarization curves revealed the existence of a passive layer formed onto the steel, composed mainly of Cr2O3, FeCr2O4, NaCrO4 and K2Fe2O4. Corrosion current density values increased, whereas the polarization resistance value decreased more than one order of magnitude as the testing temperature increased. EIS tests indicated a charge transfer controlled corrosion process, regardless of the testing temperature, and that the double electrochemical layer resistance decreased with the temperature.